Barbados : 2019 Article IV Consultation, Second Review Under the Extended Arrangement, Request for Completion of the Financing Assurances Review, and Modification of Performance Criteria-Press Releases; Staff Report; and Statement by the Executive Director for Barbados. (IMF Staff Country Reports; Country Report ;, 2019)
This paper presents 2019 Article IV Consultation with Barbados and its Second Review Under the Extended Arrangement, Request for Completion of the Financing Assurances Review, and Modification of Performance Criteria. The Article IV discussions focused on fiscal adjustment, medium-term growth and resilience to climate change and natural disasters. The Barbadian authorities continue to make good progress in implementing the comprehensive Economic Recovery and Transformation (BERT) plan aimed at restoring fiscal and debt sustainability, rebuilding reserves, and increasing growth. All program targets for end-June and end-September 2019 have been met. All three structural benchmarks for the second review have also been met. The authorities have continued the reform of state-owned enterprises (SOEs) by completing a review of tariffs and fees charged by SOEs, tightening reporting requirements, and reducing costs. The authorities reached agreement with the External Creditor Committee on a restructuring of external debt to private creditors in October 2019 and launched a debt exchange offer in early November. The IMF Staff proposes modification of the performance criteria relating to the primary balance, net international reserves and net domestic assets.